An integrated approach to redesign inventory management strategies for achieving sustainable development of small and medium‐sized enterprises: Insights from an empirical study in India. Issue 4 (8th March 2022) - Narkhede, Ganesh; Rajhans, Neela
Abstract: Efforts to incorporate inventory management (IM) strategies in small and medium‐sized enterprises (SMEs) are very limited due to the lack of cost‐effective and easy‐to‐use techniques. This research article suggests an effective and proven IM strategy that can improve the productivity and competitiveness of SMEs. The purpose of this research article is twofold: first, to develop an integrated IM strategy for SMEs to reduce inventory carrying costs; second, to design individual replenishment policies for each product. This article discusses an integrated approach considering rank order clustering (ROC) technique, a forward version of the Wagner–Whitin (W–W) lot‐sizing algorithm, and quantity discounts. First ROC is used to form clusters of different assemblies consisting of common components for aggregating the demand. The W–W algorithm is tested next over 1 year of time horizon followed by quantity discounts. Insights derived from a case study proved that the proposed integrated IM approach could save a substantial amount of total cost compared to the existing purchase policy. In addition, this approach can be a promising approach to determine appropriate replenishment quantities for each planning period. In addition, stock‐out situations can be minimized. The novelty of this study is that it proposes a practical, simple‐to‐implement, and proven IM technique for increasing productivity and achieving sustainable development of SMEs, which are working in growing economies like India.